Religious fundamentalism and political extremism - Weinberg, Leonard, 1939-; Pedahzur, Ami (Cass series--totalitarian movements and political religions., 2004)
This volume explores the relationships between fundamentalist religious belief, political extremism and outbreaks of religiously inspired violence.